Neonicotinoid Effects on Soil Microorganisms: Responses and Mitigation Strategies - Briceño Muñoz, Gabriela Elizabeth (2024)
Pesticides play a critical role in pest management and agricultural productivity; however, their misuse or overuse can lead to adverse effects on human health and the environment, including impacts on ecosystems and contamination. Currently, neonicotinoids (NNIs) are the most widely used systemic insecticides and are questioned worldwide for their possible impacts on pollinators. After NNI application, a substantial portion is not absorbed by the plant and may accumulate in the soil, affecting the soil microbial community. In this review, we explore the main studies carried out either in the laboratory or in the field about this matter. The studies report that the application of NNIs affects soil microbial activity and can act on microbial communities differently due to their unique chemical properties, degradation in soil, soil type, effects on soil properties, and methods of application. NNIs alter the diversity, structure, and abundance of soil microbes, in some cases increasing or decreasing their representativeness in soil. Bacterial phyla like Pseudomonadota, Bacillota, Actinomycetota, and Nitrospirota increase after NNI exposure, just like the families Nitrosomonadaceae, Nitrososphaeraceae, Nitrospiraceae, Sphingomonadaceae, Streptomycetaceae, and Catenulisporaceae. At the bacterial genus level, Nitrospira was associated with a decrease in nitrification processes in soil. The bacterial genera Sphingomonas, Streptomyces, Catenulispora, Brevundimonas, Pedobacter, and Hydrogenophaga are related to NNI degradation after application. Microorganisms could minimize the impacts of NNIs in agricultural soil. Therefore, the use of bioinoculation as a bioremediation tool is explored as an alternative to contribute to agricultural sustainability.